2023
DOI: 10.1101/2023.07.29.547699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial pathogens deliver water/solute-permeable channels as a virulence strategy

Abstract: Many animal and plant pathogenic bacteria utilize a type III secretion system to deliver effector proteins into the host cell. Elucidation of how these effector proteins function in the host cell is critical for understanding infectious diseases in animals and plants. The widely conserved AvrE/DspE-family effectors play a central role in the pathogenesis of diverse phytopathogenic bacteria. These conserved effectors are involved in the induction of water-soaking and host cell death that are conducive to bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…In this and a related study [53], we provide evidence that these two distinct pathogenic processes may influence each other at some level. In particular, we found that the min7 and hlb1 mutant leaves contain higher water content (this study) and transient apoplast water supplementation, which mimics HopM1-mediated water-soaking during infection, was sufficient to suppress callose deposition elicited by flg22 [53] thereby phenocopying characteristic effects of HopM1 on immune responses. There seems to be "cross-talk" between immune responses and water availability in the apoplast.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In this and a related study [53], we provide evidence that these two distinct pathogenic processes may influence each other at some level. In particular, we found that the min7 and hlb1 mutant leaves contain higher water content (this study) and transient apoplast water supplementation, which mimics HopM1-mediated water-soaking during infection, was sufficient to suppress callose deposition elicited by flg22 [53] thereby phenocopying characteristic effects of HopM1 on immune responses. There seems to be "cross-talk" between immune responses and water availability in the apoplast.…”
Section: Discussionsupporting
confidence: 63%
“…These studies led to a new model for Pst DC3000 pathogenesis in susceptible plants: Pst DC3000 translocates at least two functional groups of effectors into the host cell: one group, exemplified by AvrPto, suppresses immune signaling [61,63], whereas the other group, such as HopM1, induces the formation of an aqueous apoplast [16,64]. In this and a related study [53], we provide evidence that these two distinct pathogenic processes may influence each other at some level. In particular, we found that the min7 and hlb1 mutant leaves contain higher water content (this study) and transient apoplast water supplementation, which mimics HopM1-mediated water-soaking during infection, was sufficient to suppress callose deposition elicited by flg22 [53] thereby phenocopying characteristic effects of HopM1 on immune responses.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation